Contribuições da paisagem geográfica para a mudança de percepção de Charles Darwin sobre a natureza - Machado, João Rodolfo Von Fruhauf (2019)
With the aim of contributing to geographical thought, we sought to point in this research relevant experiences concerning the passage of Charles Darwin through South America (1832-1835) that could indicate a direct or indirect influence of Geographic Landscape in the relativization of the perspectives of Charles Darwin (1809-1882) on how the functioning of the biological world is given. This study sought to point out elements of such experiences obtained through the South American landscapes that contributed to the development of the five main forming theories of the Theory of Evolution and the consequent conversion of Charles Darwin into an evolutionist in this process. In this regard, by means of bibliographical researches that dealt about the description of the journey and later reflections on it, we seek to expose facts, analogies of Charles Darwin between the physical and the biological world, experiences and moments of his reflections that, somehow, could contribute to his gradual change of perspective on nature and the construction of his theory. Changes that transformed him from a fixist, submerged in the prevailing beliefs of his time, already in the first two years after his arrival in England